(untitled) (Global Journal of Science Frontier Research, 2023)
This study sought to examine the key constraints that affect climate financing notions of climate justice and injustice as well as how global climate finance can effectively be deployed to meet the coping requirements of vulnerable spaces and groups The study sought to design a comprehensive framework that will guide stakeholders in the climate finance and climate justice space to help in their research and practice The study was framed within the qualitative approach and deploys the critical stage review by synthesizing from secondary sources of data Key indicators were originally elicited in their unclassified form which was subsequently organized into a three-point framework In other words effective climate financing that takes into account climate justice requires Systems approach Verification mechanisms and Equity philosophy which we have used to design the the SAVE framework well discussed in the paper We conclude that finances flowing from the rich economies to poor and vulnerable regions are only a starting point for effective climate actions the efficacy of the process depends on the commitment to identify the real vulnerable people and areas commitment to expend the requisite resources appropriately the technical capacity to effectively enforce interventions followed by quality assurance measures through sound evaluation and corrective measures